Mapping of lakes in the Qinghai-Tibet Plateau from 2016 to 2021: trend and potential regularity - Zhichong Yang; Si-Bo Duan; Xiaoai Dai; Yingwei Sun; Meng Liu (International Journal of Digital Earth, 2022)
Lakes over the Qinghai-Tibet Plateau (TP) have large quantities and areas. As an important component of fragile plateau ecosystems, these lakes have attracted increasing attention. However, owing to the limitations of technology and methods, changes in smaller lakes on the TP have received less attention. In this study, we used Google Earth Engine (GEE) with the Analysis Ready Data (ARD) preparation framework to obtain preprocessed Sentinel-1 data covering the plateau. The D-LinkNet framework was introduced to achieve lake extraction, and the lake dataset was completed from 2016 to 2021. The lake dataset showed an area accuracy of 86.49% and Intersection over Union (IoU) of 0.72-0.99 in different regions. The findings were as follows: during the study period, the TP lakes tended to be stable after increasing, with an increase in area and number of +7.6% and +14.8%. Except for the northwest TP, the other regions show the same general trend. In particular, the Tarim Basin exhibited a lake variation pattern independent of the TP. Significantly, we found frequent lake activity in the Kunlun Mountains, Qaidam Basin, Mountain Qogir, etc. Effects of the ongoing La Niña event on the TP lakes may occur in the next few years.